Bentuk Interferensi Bahasa Siswa Dalam Berargumentasi Saat Pembelajaran Bahasa Indonesia - Sadimin, Sadimin, Laili Etika Rahmawati, S.Pd., M.Pd (2016)
FORM OF INTERFERENCE IN THE LANGUAGE STUDENT LEARNING TIME ARGUED INDONESIAN Skripsi Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Surakarta Mei, 2016 This study examines the forms of language interference that occurs in junior high students in arguing when learning Indonesian. The research subject is class VIII D SMPN 2 Kartasura with the number of 32 students. This study uses a unified referential. This type of research is qualitative descriptive. This study aims to (1) describe the shape of the interference languages class VIII D at SMP Negeri 2 Kartasura in arguing when learning Indonesian, (2) Describing the background to interference languages class VIII D at SMP Negeri 2 Kartasura in arguing when learning English Indonesia. Mechanical validity of the data using triangulation theory. Data analysis technique used is the analysis of qualitative data. Based on the research results can be concluded that the form of language interference eighth grade D there are two: (1) over the code, (2) mixed code. Interference of this language is derived from the Javanese language as the majority of students came from Java, whereas the factors behind the occurrence of interference there are eight: (1) do not master the vocabulary of Indonesian, (2) lingungan family, school, and neighborhood of residence, (3) Friends peer, (4) the habit of communicating with the Java language and Indonesia, (5) itself due to mix the two languages seem funny and break the ice (6) profession of parents, (7) the mother tongue that started small are used to communicate, and ( 8) heredity. The conclusions of this study is getting students accustomed to using two or more languages, the greater the chances of interference languages. Interference is not wrong to do as long as it is placed in the appropriate situation. Keywords: interference, arguments, code-mixing, code switching